2013
DOI: 10.1101/cshperspect.a008755
|View full text |Cite
|
Sign up to set email alerts
|

The Endolysosomal System in Cell Death and Survival

Abstract: The endocytic pathway is a system specialized for the uptake of compounds from the cell microenvironment for their degradation. It contains an arsenal of hydrolases, including proteases, which are normally enclosed in membrane-bound organelles, but if released to the cytosol can initiate apoptosis signaling pathways. Endogenous and exogenous compounds have been identified that can mediate destabilization of lysosomal membranes, and it was shown that lysosomal proteases are not only able to initiate apoptotic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
76
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(80 citation statements)
references
References 102 publications
1
76
0
3
Order By: Relevance
“…19 CTSL and other lysosomal proteases are released into the cytosol upon apoptosis induction. 23 The fact that FH does not become degraded within the apoptotic cells implies that it remains functional after internalization. Indeed, we found that FH acts as cofactor for CTSL-mediated cleavage of C3 into C3b, which may be due to direct binding of FH to CTSL.…”
Section: Discussionmentioning
confidence: 99%
“…19 CTSL and other lysosomal proteases are released into the cytosol upon apoptosis induction. 23 The fact that FH does not become degraded within the apoptotic cells implies that it remains functional after internalization. Indeed, we found that FH acts as cofactor for CTSL-mediated cleavage of C3 into C3b, which may be due to direct binding of FH to CTSL.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of functional retromer, autophagy and lysosomal degradative capacity are perturbed leading to abnormal accumulation of material in lysosomes and lysosomal storage diseases [105]. The lysosomes are also of vital importance to the cell as they can trigger apoptotic cell death when their integrity or functions are compromised [106][107][108].…”
Section: Snx1 and Snx2mentioning
confidence: 99%
“…Highly reactive ROS produced in lysosomes as a result of Fenton-type reactions can damage the lysosomal membrane and induce release of lysosomal cargo into the cytosol, thereby promoting apoptosis (Repnik et al, 2013). Overall, this leads to a point of no return during the commitment stage of apoptosis and suggests that apoptosis induced by tirucallic acids proceeds mainly through the mitochondrial pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Rapamycin, which promotes autophagy, even protects cells against a range of proapoptotic insults. It is believed that autophagy, which enhances clearance of mitochondria, reduces cytosolic cytochrome c release and downstream caspase activation thereby promoting survival (Repnik et al, 2013). All forms of autophagy, in turn, rely on lysosomes for the subsequent degradation of their cargo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation